Implementing Path of Building the Strategic Fulcrum of the World Marine Talent Centers and Innovation Hubs - XU Shiyuan; MENG Rongyi; LI Yong (Haiyang Kaifa yu guanli)
It is urgent to implement path of building the strategic fulcrum of the world marine talent centers and innovative hubs to lead the construction of a maritime power and promote the great rejuvenation of the Chinese nation. This paper uses literature research and deductive reasoning to construct the implementation path of building the world marine talent center and the strategic fulcrum of innovative highland. Firstly, the theoretical connotation of building this strategic fulcrum is systematically explained from three aspects: the gathering of marine talents, the source of marine innovation and the development of marine undertakings. Secondly, the significance of building this strategic fulcrum is analyzed from the perspective of the implementation of the strategy of strengthening the country with talents, the strategy of innovation-driven development and the construction of a maritime power. Thirdly, under the premise of following the principles of innovation, systematicness and feasibility, it is clear that the goal of building this strategic fulcrum is resource gathering, science and technology innovation, development leading and radiation driving. Finally, the key measures to build a strategic fulcrum, such as building a world marine talent center, building a marine innovation highland, and promoting the development of strategic fulcrum, are emphatically put forward.